THE EFFECT OF CONTEXTUAL TEACHING AND LEARNING (CTL) MODEL ON BIOLOGY LEARNING OUTCOMES OF BACTERIA CONCEPTS IN CLASS X STUDENTS OF MA ALIYAH ALHILAL NAMLEA) - Syafa Lisaholit; Siti Hajar Loilatu (Sean Institute, 2023)
Contextual teaching and learning (CTL) learning model on learning outcomes of bacterial concepts in Class X MA Aliyah alhilal namlea Students This type of research is a Quasi Experiment research that aims to determine the effect of Contextual Teaching and Learning (CTL) learning model on biology learning outcomes of bacterial concepts in class X MA Aliayah Alhilal Namlea students. The sample in this study amounted to 22 students selected using random sampling technique. The data collection technique used was a test consisting of 30 items of multiple choice questions pretest and posttest with data processing techniques normality test, homogeneity test and hypothesis testing using SPSS (Statistical Product and Service Solutions) version 25. The results showed that there was a positive and significant effect of the Contextual Teaching and Learning learning model on the learning outcomes of the biology of the concept of bacteria in class X MA Aliyah alhilal Namlea students. This can be seen from the total percentage obtained before being given treatment in the excellent, good, sufficient and deficient categories, namely 0% and after being given treatment in the posttest experimental class reached 82% in the excellent category, in the good category 9.09% in the sufficient category 4.54% in the deficient category reached 4.54. The results of the normality test for the experimental class with a Sig level of 0188 while for the control class 0.200%. The results of the experimental class homogeneity test with Sig level pretest 0.352 and posttest 0354. In hypothesis testing using the t test with a significant value of 0.00 <0.05, it is known that the t value is 9.909 and the t table is 1.72472, it can be assumed that the effect of the CTL learning model affects student learning outcomes.